AFROCENTRIC PRINCIPLES AND THE MEMORY OF QUILOMBOS IN ANTÔNIO BISPO DOS SANTOS'S "THE LAND GIVES, THE LAND WANTS": A LEGACY OF POWER - Melo, Duília de Jesus Lopes; Silva, Maria Cecilia de Paula (Seven Editora, 2025)
This work is an exercise in analyzing how Afrocentric principles emerge as possible reflections in the memories and language contained in the work of Antônio Bispo. We also aim to highlight concepts presented that corroborate the writer's own life trajectory as a political actor, as well as to analyze how and whether the themes of education and racism are evoked in the work. The methodological approach is bibliographic and seeks to be consistent in conducting this qualitative work, where we also present contributions from other authors. The proposal of this work is an invitation to a counter-colonial education, as we are presented with concepts such as the confluence of knowledge, cosmophobia, colonialism of submission, among others. Furthermore, it approaches in a very particular way the central thought and principles of Afrocentrism proposed by Asante (2019). This work presented itself as a sophisticated framework for issues of memory, racism, and education, since it proposes strategies for an education that aims to be counter-colonial and Afrocentric.DOI: https://doi.org/10.56238/sevened2025.038-018